Respostas
respondido por:
3
a1 = 4
a2 = 11
r = a2 - a1
r = 11 - 4
r = 7
an = a1 + (n - 1) . r
an = 4 + (n - 1) . 7
an = 4+ 7n - 7
an = 7n - 3
a2 = 11
r = a2 - a1
r = 11 - 4
r = 7
an = a1 + (n - 1) . r
an = 4 + (n - 1) . 7
an = 4+ 7n - 7
an = 7n - 3
respondido por:
0
Numa PA PA em estudo
an = a1 + (n - 1).r a1 = 4
an = 18
n = 3
r = 7 (18 - 11 = 11 - 4 = 7)
an = 4 + (n - 1).7
an = 4 + 7n - 7
an = 7n - 3
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás